Pertuzumab, trastuzumab, and docetaxel in HER2-positive metastatic breast cancer - Swain, Sandra M.; Schneeweiss, Andreas (The New England journal of medicine, 2015)
In a randomized trial comparing pertuzumab, trastuzumab, and docetaxel with placebo, trastuzumab, and docetaxel, the pertuzumab combination resulted in a median overall survival of 56 months in women with metastatic HER2-positive breast cancer.
Gesehen am 19.07.2017